The early posterior cortex pixel value ratio: a novel reliable indicator for distraction osteogenesis - Liu, Ze; Liu, Qi; Wang, Min; Zhou, Chenhan; Guo, Hongbin; Liang, Jieyu; Zhang, Yi (Frontiers in Surgery, 2023)
Aims: To explore the associations of the early PVR in four cortices with Healing Index (HI), Lengthening Index (LI), and External Fixator Index (EFI) in the bone union and nonunion group. Methods: A total of 52 patients, including 39 bone union and 13 bone nonunion subjects, were recruited in this study. The general characteristics and PVR in four cortices in each group was explored. Afterwards, the early PVR in four cortices, including medial, lateral, anterior and posterior side, were compared. Finally, the associations of the early PVR in four cortices with HI, LI, EFI were also investigated. Results: The general characteristics of these patients were consistent, except for HI (31.54±12.24 VS 45.08±27.10, P=0.018) and EFI (57.63±18.15 VS 71.29±24.60, P=0.046). The growth of regenerated callus was asymmetrical in bone union group (the posterior PVR seems to grow faster), whereas no statistical difference was obtained in bone nonunion group. Furthermore, the posterior PVR in bone union group was significantly higher than that in bone nonunion group (the first month: 0.96±0.17 vs 0.86±0.06, p=0.047; the second month: 0.98±0.14 vs 0.89±0.09, p=0.041; the third month: 1.00±0.12 vs 0.92±0.09, p=0.039). Most importantly, the posterior PVR was inversely associated with HI, LI, and EFI (the first month: r=-0.343, p=0.041; r=-0.346, p=0.042; r=-0.352, p=0.041; the second month: r=-0.459, p=0.004; r=-0.277, p=0.101; r=-0.511, p=0.002; the third month: r=-0.479, p=0.003; r=-0.398, p=0.018; r=-0.551, p=0.001) in bone union group, respectively. However, this finding was lost in bone nonunion group. Conclusion: The early posterior cortex PVR seems to grow faster than medial, lateral and anterior side in the bone union, which represents an asymmetrical development pattern. Moreover, the posterior cortex PVR was negatively associated with HI, LI and EFI, respectively. The posterior cortex PVR may be a novel and reliable detection index in the process of DO.